(untitled) (INNOVATIVE ECONOMY, 2020)
Grynchuk Yu.S., Tkachenko K.V., Drahan O.O. ORGANIZATIONAL AND ECONOMIC FACTORS FOR IMPROVING THE SUSTAINABILITY OF GRAIN PRODUCTION IN UKRAINE Purpose. The aim of the article is the development of theoretical, methodological provisions and practical recommendations for ensuring the stability of grain production at agricultural enterprises. Methodology of research. General scientific and special methods of economic research are used in the article, in particular: a systematic approach – in studying the connections between phenomena and processes in the system of ensuring economic stability of enterprises; statistical analysis – in determining the dynamics, structure and effectiveness of the development of agricultural enterprises for the production of grain and infrastructure; grouping – to determine the impact of various factors on the level of efficiency of grain production; comparative – for the comparison of economic phenomena in different time periods in order to identify the cause-effect relationship; dialectical, abstract and logical – when conducting theoretical generalizations. Findings. The directions of achievement and increase of economic stability of agricultural enterprises for grain production are substantiated, taking into account the results of estimation of its parameters, the level of adaptation to the changing changes of the external and internal environment on the basis of modernization of the state regulation instruments of the industry and the full use of internal reserves by the commodity producers for increasing the efficiency of production, as well as strengthening information and analytical function of economic regulation. It is proposed to create an organizational subsystem within the framework of the general control system to increase the efficiency of management of the economic stability of agricultural enterprises for the production of grain, in which the important components are risk management and a system of quantitative indicators. Originality. The methodical approach of the complex estimation of the potential of the agricultural enterprise for ensuring the stability of grain production is determined, which will enable the use of operational management tools such as organizational and coordinating, planning, information and analytical ensuring the balance of interests of structural and functional subsystems, which will increase economic stability in the long-term perspective. Practical value. The obtained research results can be used for the development of sectoral and regional programs for the development of grain production and forecasts for the production of grain in Ukraine. The indicators of stability of the grain sector, calculated in the regions of Ukraine, can be used by the management of enterprises of the corporate sector of the agrarian economy in developing the system of plans of production and economic activity. Key words: stability; economic stability; agricultural enterprise; grain production; sustainable development; efficiency of grain production; crop.